Designing hybrid CRISPR-Cas12 and LAMP detection systems for treatment-resistant Plasmodium falciparum with in silico method - Parikesit, Arli A.; Hermantara, Rio; kevin, Gregorius; Sidhartha, Elizabeth (Narra Sains Indonesia, 2023)
Genes associated with drug resistance of first line drugs for Plasmodium falciparum have been identified and characterized of which three genes most commonly associated with drug resistance are P. falciparum chloroquine resistance transporter gene (PfCRT), P. falciparum multidrug drug resistance gene 1 (PfMDR1), and P. falciparum Kelch protein K13 gene (PfKelch13). Polymorphism in these genes could be used as molecular markers for identifying drug resistant strains. Nucleic acid amplification test (NAAT) along with DNA sequencing is a powerful diagnostic tool that could identify these polymorphisms. However, current NAAT and DNA sequencing technologies require specific instruments which might limit its application in rural areas. More recently, a combination of isothermal amplification and CRISPR detection system showed promising results in detecting mutations at a nucleic acid level. Moreover, the Loop-mediated isothermal amplification (LAMP)-CRISPR systems offer robust and straightforward detection, enabling it to be deployed in rural and remote areas. The aim of this study was to develop a novel diagnostic method, based on LAMP of targeted genes, that would enable the identification of drug-resistant P. falciparum strains. The methods were centered on sequence analysis of P. falciparum genome, LAMP primers design, and CRISPR target prediction. Our designed primers are satisfactory for identifying polymorphism associated with drug resistant in PfCRT, PfMDR1, and PfKelch13. Overall, the developed system is promising to be used as a detection method for P. falciparum treatment-resistant strains. However, optimization and further validation the developed CRISPR-LAMP assay are needed to ensure its accuracy, reliability, and feasibility